Annual report to the Government of Antigua and Barbuda 1988 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
The documents presents a general information, a history of IICA in Antigua and Barbude. Continuously, it presents a summary of report and the presentation of the following technical cooperation projects: 1) Support for the organization and management of technology generation and transfer in the OECS; 2) Strengthening farmer organizations in the OECS; 3) Strengthening plant protection and quarantine capabilities in the Windward Inslands and Antigua and Barbuda for the marketing of non-traditional crops. Then, the presentation of the following short term activities: 1) OECS diversification programme; 2) Agricultural sector assessment for project identification Antigua and Barbuda and St. Vincent and the Grenadines; 3) Validation of sheep production systems - Dominica; 4) Interim management of Amblyomma variegatum eradication (Dominica, St. Lucia); 5) Improved management of inter-personal relationships St. Lucia; and, 6) A pilot study of farm incomes - Grenada. Finally, training participation, project unit/regional projects, staff and expenditure.